Empowering Listening Comprehension through Pre-Listening Strategies: An Action Research Study on EFL Learners - Ruisah (IJLHE: International Journal of Language, Humanities, and Education, 2025)
Listening comprehension remains one of the most challenging language skills for English as a Foreign Language (EFL) learners. This action research study explores the impact of pre-listening language learning strategies on the listening comprehension skills of first-semester students at Universitas Pamulang. A total of 35 students participated in a structured intervention comprising three cycles of strategy-based listening instruction. Data were collected through observation forms, researcher-practitioner journals, and semi-structured interviews. Descriptive and content analyses were employed to interpret the data. The findings reveal that the explicit teaching of pre-listening strategies significantly improved learners’ motivation, comprehension, and engagement with listening tasks. Students reported increased confidence, enhanced understanding of listening texts, and reduced anxiety. Although a few learners faced challenges in recalling prior knowledge or vocabulary, the majority expressed positive attitudes toward the approach. The study highlights the value of incorporating pre-listening strategies as an integral component of EFL instruction to support listening development and learner autonomy.